Predicting turnover intention among generation z employees based on psychosocial work environment factors - Riamanda, Irin; Syahara.Z, Yesti; Yazid, Sulthanul (Jurnal Ilmiah Psikologi Terapan, 2025)
As Generation Z enters the workforce, high turnover rates pose challenges for organizations. Psychosocial work environment factors are linked to turnover intention, yet their predictive role among Generation Z employees remains understudied. This study examined key psychosocial work environment factors influencing turnover intention among Generation Z employees in Banda Aceh. Using binary logistic regression on data from 315 respondents, the model explained 65.3% of the variance in turnover intention. Three significant predictors emerged: job satisfaction, horizontal trust, and insecurity over working conditions. Job satisfaction served as a protective factor, aligning with Generation Z’s emphasis on meaningful work and work-life balance. Horizontal trust enhanced emotional attachment to the organization through supportive peer relationships. In contrast, insecurity over job stability and wages increased stress and turnover intention. Notably, 79.37% of respondents reported low turnover intention, likely influenced by limited job opportunities and high competition in small cities. Longer tenure was also associated with lower turnover intention. These findings highlight the importance of addressing psychosocial work environment factors to strengthen retention strategies for Generation Z employees.